1982
DOI: 10.1083/jcb.93.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Laminin, fibronectin, and collagen in synaptic and extrasynaptic portions of muscle fiber basement membrane.

Abstract: Light and electron microscope immunohistochemical methods were used to study the distribution of several proteins in rat skeletal muscle . The aims were to identify components of muscle fiber basement membrane and to compare the small fraction (0 .1%) of the basement membrane that extends through the synaptic cleft at the neuromuscular junction with the remaining, extrasynaptic portion . Synaptic basement membrane is functionally specialized and plays important roles in neuromuscular function and regeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
1
5

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(136 citation statements)
references
References 46 publications
6
124
1
5
Order By: Relevance
“…The resolution of this form of immunocytochemistry is insufficient to determine rigorously whether staining was associated with the synaptic cleft or with other connective tissue adjacent to the neuromuscular junction. Fibronectin may, however, in addition to its location in reticular connective tissue, also be present in muscle basal lamina (39). In contrast to the above observations, neither antigen-39 nor antigen-35 appeared to extend into the synaptic cleft or show obvious accumulation in the synaptic region (data not shown).…”
Section: Distribution Of Antigens In Vivocontrasting
confidence: 52%
See 1 more Smart Citation
“…The resolution of this form of immunocytochemistry is insufficient to determine rigorously whether staining was associated with the synaptic cleft or with other connective tissue adjacent to the neuromuscular junction. Fibronectin may, however, in addition to its location in reticular connective tissue, also be present in muscle basal lamina (39). In contrast to the above observations, neither antigen-39 nor antigen-35 appeared to extend into the synaptic cleft or show obvious accumulation in the synaptic region (data not shown).…”
Section: Distribution Of Antigens In Vivocontrasting
confidence: 52%
“…Moreover, studies of regenerating nerve and muscle have suggested that elements of the synaptic basal lamina can induce both the differentiation of regenerating nerve terminals (40) and the accumulation of the acetylcholine receptor (AChR) l within the postsynaptic membrane (3,8). When immunohistochemical techniques were employed to compare synaptic and extrasynaptic basal lamina, some antigenic determinants were detected in both regions, some were detected only in extrasynaptic regions, and some appeared to be limited to synaptic basal lamina (39,41). Since most of the synaptic antigens have been defined only by serological criteria, their biochemical identities remain unknown.…”
mentioning
confidence: 99%
“…Diversity was observed in intrafusal basal laminas in reference to time of appearance, proportional representation of compounds at various loci, and occurrence of different isoforms. These findings are consistent with previous reports (Sanes and Cheney, 198213;Engvall et al, 1990;Sanes et al, 1990;Brubacher et al, 1991;Glukhova et al, 1993;Vanden Heuvel and Abrahamson, 1993) on variations of basal lamina structure and composition in extrafusal muscle and other tissues.…”
Section: Discussionsupporting
confidence: 94%
“…We examined whether Electrophorus or bovine acetylcholinesterase would interact with collagens, fibronectin or laminin. These proteins were purified from a mouse tumor (Engelbreth-Holm-Swarm), which produces large amounts of basement membrane components, o r from human placenta [21]. The experiments were done in two ways: either using radioactive iodinated matrix proteins, with an excess of acetylcholinesterase (Tables 2 and 3), or following only the enzyme's activity in sucrose gradients, in the presence of an excess of cold proteins (Table 4).…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…Laminin and fibronectin have been demonstrated immunohistologically at the surface of Electrophorus electroplaques, with a distribution similar to that of acetylcholinesterase [20]. The same proteins together with type IV collagen are found also in the synaptic regions of rat skeletal muscle while type V collagen appears restricted to the extrasynaptic regions [21].…”
mentioning
confidence: 99%